Why Is Russia blocking Ukraine's food exports? - Welsh, Caitlin; Glauber, Joseph W.; Dodd, Emma (Center for Strategic and International Studies, 2023)
Russia’s termination of the Black Sea Grain Initiative (BGSI) will be a main topic of discussion in United Nations General Assembly meetings next week. The United Nations and others continue to urge Russia to rejoin the deal, while Russia declares its willingness to rejoin if its demands are met. It likely has no such intention. Continuing to block Ukraine’s agricultural exports is in Russia’s economic and political interest while Russia manipulates its own food exports to appease food-importing countries. And its exit from the deal has not contributed to a global food price spike—for now.